Measuring Student Character in a Fair and Contextual Manner: Development of Local Culture-Based Instruments with the IRT Model - Toron, Vinsensius Bawa; Marzuki, Marzuki; Muhson, Ali; Bria, Florens Maxi Un; Bhoki, Hermania; Waton, Fidelis Regi (Journal of Innovation in Educational and Cultural Research, 2026)
The importance of character education in the formation of a generation that is intellectually endowed but also morally and socially accountable should not be underrated. Nonetheless, evaluating student character remains a problem, especially across diverse local cultural backgrounds. In this research, an attempt was made to come up with a measure of character among junior high school students based on the local cultural values, and to achieve this purpose, the current psychometric theory of the item Response Theory (IRT) was used in the development of the instrument, as well as expert and data validation through interviews, questionnaires, and observations. The Generalised Partial Credit Model (GPCM) was the most suitable as determined in the analysis, and all the 68 items were highly conforming. The unidimensionality assumption was met (MSA = 0.977; first-factor variance = 77.57%), and the parameter correlations implied invariance and fairness across student groups. The instrument has a total information value of 403.08, a standard error of 0.05, and an information area probability of 98.52%, which indicates high precision and coverage of the measurement. Qualitative findings proved cultural relevance and semantic clarity. The study will contribute to the field of educational evaluation by offering a valid, reliable, and culture-adaptive tool that can serve as a guide for both research and research-practice in character education across diverse settings.